2022
DOI: 10.3390/molecules27020471
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Investigation of Bile Acid-Paclitaxel Hybrids

Abstract: Chenodeoxycholic acid and ursodeoxycholic acid (CDCA and UDCA, respectively) have been conjugated with paclitaxel (PTX) anticancer drugs through a high-yield condensation reaction. Bile acid-PTX hybrids (BA-PTX) have been investigated for their pro-apoptotic activity towards a selection of cancer cell lines as well as healthy fibroblast cells. Chenodeoxycholic-PTX hybrid (CDC-PTX) displayed cytotoxicity and cytoselectivity similar to PTX, whereas ursodeoxycholic-PTX hybrid (UDC-PTX) displayed some anticancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Fourthly Melloni et al [17], illustrated that CDC-PTX along with UDC-PTX in combination with paclitaxel, an anti cancer agent led to apoptosis induction in leukaemia HL60 cells along with NB4 acute promyelocytic leukaemia cells via a high output condensation reaction of CDCA along with UDCA (Figure 3E). Additionally, it was illustrated that CDC-PTX along with UDC-PTX RKO led to apoptosis induction in HCT-116 colonic carcinoma cells.…”
Section: Cell Death Modes Of Synthetic Bile Acids Prototypical Agents...mentioning
confidence: 96%
See 1 more Smart Citation
“…Fourthly Melloni et al [17], illustrated that CDC-PTX along with UDC-PTX in combination with paclitaxel, an anti cancer agent led to apoptosis induction in leukaemia HL60 cells along with NB4 acute promyelocytic leukaemia cells via a high output condensation reaction of CDCA along with UDCA (Figure 3E). Additionally, it was illustrated that CDC-PTX along with UDC-PTX RKO led to apoptosis induction in HCT-116 colonic carcinoma cells.…”
Section: Cell Death Modes Of Synthetic Bile Acids Prototypical Agents...mentioning
confidence: 96%
“…Additionally, various laboratories have generated innovative Bile Acid obtained substance for evaluation of the tumor suppressive actions of bile acids. These substances were illustrated to result in induction of programmed cell death (PCD) in different cancer cells besides possess tumor repressive action [14][15][16][17][18][19][20][21][22][23][24]. Cell death possesses a key part in embryonic formation, sustenance of homeostasis, as well as elimination of injured cells.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, Melloni et al [25] showed that CDC-PTX and UDC-PTX combined with paclitaxel (PTX), an anticancer drug, induced apoptosis in HL60 and NB4 acute promyelocytic leukemia cells through a high-yield condensation reaction of CDCA and UDCA (Figure 3E). It was also shown that CDC-PTX and UDC-PTX RKO induced apoptosis in HCT-116 colon cancer cells.…”
Section: Cell Death Mechanism Of Synthetic Bile Acid Derivatives In C...mentioning
confidence: 99%
“…In addition, several laboratories have synthesized novel bile acid derivatives to explore the tumor-suppressive function of bile acids. These derivatives were shown to induce programmed cell death in several cancer cells, and have tumor-suppressive effects [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Since cancer cell proliferation and apoptosis are regulated by cellular signals, the inhibition of these signals is helpful for eliminating cancer [35]. It is worth adding that some other conjugated taxanes were reported recently, such as two novel conjugated derivatives of Chenodeoxycholic acid-Paclitaxel and Ursodeoxycholic acid-Paclitaxel that displayed similar or lesser anticancer activity compared to Paclitaxel [36], and Docetaxel-Palmitate-conjugated derivative [37] that offered a decreased IC50 compared to that of Docetaxel. IDD-1010 at a low concentration (10 nM) inhibited cell proliferation and arrested proliferating PC3-Luc cells in vitro at the G1-phase.…”
Section: In Vitro Drug Activitymentioning
confidence: 99%